Associations of Dairy Consumption and Cognitive Function in the Boston Puerto Rican Health Study. (14th June 2022) - Kenny, Sophie; Scott, Tammy; Aytur, Semra; Garelnabi, Mahdi; Bhadelia, Rafeeque; Guan, Yi; Koo, Bang-Bon; Zhang, Xiyuan; Tucker, Katherine; Bigornia, Sherman
Abstract: Objectives: To examine the cross-sectional and prospective associations between dairy consumption and cognitive function among Puerto Rican adults. Methods: Data are from the Boston Puerto Rican Health Study (57 yrs, 71% female), an ongoing prospective cohort study. Diet was assessed using a validated food frequency questionnaire. Dairy products included milk, cheese, yogurt, cream, and butter. Our dairy exposures were total dairy (s/d), regular & reduced fat dairy (s/d), and nonfat dairy products (s/d). A battery of neurocognitive tests was administered by trained staff in the language of preference. Global cognitive function score (GCS) was calculated as the mean z-scores of the individual tests. A subset of BPRHS participants returned for neurocognitive testing at 13-yr follow-up. For the current study, we examined the baseline cross-sectional associations between dairy and GCS (n = 1067) and the prospective associations of dairy consumption (averaged of baseline and 2-yr FFQ data) with GCS at 13 years (n = 433). Multivariable linear regression models were adjusted for age, sex, education, smoking, physical activity, energy intake, and consumption of fruits and vegetables and added sugar. Baseline GCS was additionally included in prospective models. Dairy variables were skewed, and a log-transformation was applied. Results: Average dairy consumption for total, regular & reduced fat dairy, and nonfat dairy was 2.2 s/d, 1.9, s/d, and 0.3 s/d, respectively. In cross-sectional analyses, total [β = 0.078 (0.033, 0.124), P = 0.001] and reduced & regular fat dairy [0.066 (0.020, 0.112), P = 0.005] were positively associated with GCS. Nonfat dairy was not significantly associated [0.015 (−0.001, 0.033), P = 0.210]. In prospective analyses, we observed null associations between total [−0.0134 (−0.094, 0.067), P = 0.740], regular & reduced-fat [−0.039 (−0.123, 0.046), P = 0.370], and nonfat dairy [0.0027 (−0.020, 0.026), P = 0.820] and 13-yr GCS. Conclusions: In this cohort of Puerto Rican adults, total and regular & reduced-fat dairy was associated with greater global cognitive function in cross-sectional analyses at baseline, but not after 13 years of follow-up. Additional prospective analyses are warranted to clarify these associations. Funding Sources: National Institute on Aging.